Swordbird - Fan, Nancy Yi (HarperCollins, 2007)
Warring factions of blue jays and cardinals call on Swordbird, the heroic bird of peace, to rescue them from the evil machinations of Turnatt, the tyrant hawk lord who plans to enslave them.